FACTORS CONTRIBUTING TO PULMONARY TB TREATMENT LOST TO FOLLOW-UP IN DEVELOPING COUNTRIES: AN OVERVIEW - OPPERMAN, Monique; DU PREEZ, Ilse (African Journal of Infectious Diseases (AJID), 2022)
Background: Despite the available treatment options, pulmonary tuberculosis (TB) remains a leading cause of disease-related deaths worldwide. Treatment non-adherence/lost to follow-up (LTFU), particularly in developing countries, is a continuous concern. LTFU prolongs TB infectiousness and contributes to TB treatment failure, relapse, and death. Furthermore, LTFU also delays global TB eradication by promoting TB spread and drug-resistant TB strain development. The purpose of this paper is to give an overview of the commonly observed risk factors associated with TB treatment LTFU in developing countries. Materials and Methods: A literature survey was done of studies published in the past decade, which evaluated the risk factors for LTFU in TB patients, specifically in developing countries. Results: Several variables, including socio-demographic, patient-related, TB disease and other health-related-factors, healthcare and system determinants, as well as treatment-related factors, were identified to increase the risk of TB treatment LTFU. More recently applied adherence interventions in developing countries, show potential for implementation on a larger scale. Conclusion: Successful TB treatment is contingent on treatment adherence, and by addressing these persisting LTFU risk factors, treatment adherence in developing countries may be improved.